Uncharted Territories: First report of Euwallacea fornicatus (Eichhoff) in South America with new reproductive hosts records. - Ceriani-Nakamurakare, Esteban; Johnson, Andrew J.; Gomez, Demian F. (Zootaxa, 2023)
We report the presence of the invasive ambrosia beetle, Euwallacea fornicatus (Eichhoff, 1868), for the first time in South America. The identity is established by morphological and molecular methods, although the sequences suggest that it represents a separate haplotype from the populations that have caused significant damage in South Africa, Israel, and California, and is most phylogenetically similar to specimens from Asia and greenhouses in Europe. This pest is one of the most successful invaders, causing high economic and ecological impacts in the regions where it is introduced. Our records are from the city of Buenos Aires, Argentina, one of the most populated and largest port cities in South America, where attacks by this beetle are present on a wide range of living street trees. The large number of trees attacked and the new records of reproductive host species suggest that the beetle is already established and widespread in the city’s urban forest. This context implies that the beetle may pose a threat to the urban and natural environment, as well as to the forests and fruit production of the region. Informamos la presencia del escarabajo invasor de ambrosía, Euwallacea fornicatus (Eichhoff, 1868), por primera vez en Sudamérica. La identificación se estableció mediante métodos morfológicos y moleculares, si bien las secuencias sugieren que representa un haplotipo distinto de las poblaciones que han causado daños significativos en Sudáfrica, Israel y California, resulta filogenéticamente más similar a especímenes de Asia e invernaderos de Europa. Esta plaga es una de las especies invasoras más exitosas, causando altos impactos económicos y ecológicos en las regiones donde es introducida. Nuestros registros provienen de la ciudad de Buenos Aires, Argentina, una de las ciudades portuarias más pobladas y grandes de Sudamérica, donde los ataques de este coleóptero están presentes en una amplia diversidad de especies pertenecientes al arbolado urbano. El gran número de árboles atacados y los nuevos registros de especies hospedadoras reproductoras sugieren que el coleóptero ya está establecido y extendido en el bosque urbano de la ciudad. Este contexto implica que el coleóptero puede suponer una amenaza para el medio urbano y natural, así como para los bosques y la producción frutícola de la región.